2022
DOI: 10.3389/fonc.2022.812346
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-Sparing Treatment for Endometrial Cancer or Atypical Endometrial Hyperplasia Patients With Obesity

Abstract: ObjectiveTo evaluate the efficacy and prognosis of fertility-sparing treatment on endometrial cancer (EC) and atypical endometrial hyperplasia (AEH) patients with BMI ≥ 30 kg/m2.MethodsA total of 102 EC or AEH patients with obesity who received fertility-preserving therapy in the Department of Obstetrics and Gynecology, Peking Union Medical College Hospital were included in our study. All patients were followed up regularly. Clinical characteristics, treatment outcomes, adverse events, and reproductive outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Dong et al reported on three cases treated with GnRHa plus aromatase inhibitor in whom the disease remained stable for 2 years 22. In our previous study we used GnRHa combination therapy in 61 patients with obesity and 34 patients with recurrence, and achieved a high regression rate in these patients 23 24…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Dong et al reported on three cases treated with GnRHa plus aromatase inhibitor in whom the disease remained stable for 2 years 22. In our previous study we used GnRHa combination therapy in 61 patients with obesity and 34 patients with recurrence, and achieved a high regression rate in these patients 23 24…”
Section: Discussionmentioning
confidence: 90%
“… 22 In our previous study we used GnRHa combination therapy in 61 patients with obesity and 34 patients with recurrence, and achieved a high regression rate in these patients. 23 24 …”
Section: Discussionmentioning
confidence: 99%
“…GnRH-a reduces estrogen synthesis in the gonads, while letrozole inhibits estrogen synthesis in peripheral tissues; therefore, coadministration of letrozole and GnRH-a significantly downregulates estrogen levels in premenopausal women [ 173 ]. However, the GnRH-a regimen can lead to low pregnancy rates and reduced bone mass, which limits the widespread use of GnRH-a [ 174 ].…”
Section: Potential Therapeutic Methods To Enhance Progestin Sensitivitymentioning
confidence: 99%
“…Despite this evidence, the lack of randomized clinical trials on the efficacy and safety of treatment in EC in relation to the risk of worsening oncological disease explains the cautious way to preserve fertility in these patients [ 62 ]. For obese patients with EC and AEH, a weight loss of over 10% and the administration of GnRH agonists would have an increased effect compared to progestin therapy [ 63 ].…”
Section: Fertility-sparing Management In Cancer Patientsmentioning
confidence: 99%